PENERAPAN MODEL COOPERATIVE LEARNING TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN PERILAKU BELAJAR SISWA MADRASAH TSANAWIYAH AL IKHLAS MOWEWE - Muhammad Nur (IAIN Kendari, 2018)
The object of this thesis is to research the application of cooperative learning model on learning of Islamic education in establishing students learning behaviour at Al-Ikhlash Islamic Junior High School of Mowewe. The purpose of this study is to analyze the application of Cooperative Leaning Model in establishing student learning behaviour.The research used qualitative approach, and case study method with descriptive analysis.Primary data sourcedfrom Head of Madrasah, teachers and students. While the secondary data sourced from data about the objective condition of Al-Ikhlas Islamic Junior High School of Mowewe which is detailed, processed, and analyzed. The research technique included observation, interviews, and documentation. Data is processed and analyzed through reduction, presentation, and data conclusions. Validity test data include credibility and confirmbility test.The results of this study are The application of Cooperative Learning on the Islamic education learning in student learning behaviour is done through three types: learning together, group discussion, and Jigsaw.The implication of this study is expected to inform and contribute in educational improvement. It hoped from the application of Cooperative Learning in Islamic education learning in student learning behaviour to createthe policies and wisdom to deal the complexity of learning problems.